Vidas errantes entre a loucura e a criminalidade: uma história da emergência do manicômio judiciário no estado da Paraíba - Fatima Saionara Leandro Brito (2016)
The proposal presented by this thesis is to historicize the emergence of Forensic Psychiatry Institute of Paraíba - the Judicial Asylum. Therefore, we sought to find and discuss the interlinkages, convocations, conflicts and historical threads that allowed the junction between the knowledge of justice and psychiatry, as well as assemblages posts in the social fabric that contributed to the opening of this institution August 16, 1943. Understanding the Judicial Asylum as the result of a historical process, questioned under what historical conditions the guy named crazy and criminal, to be classified as a social danger, gained visibility and has been considered a problem for the state Paraiba. Also, questioned the way he articulated the legal and psychiatric forces, through the concepts of degeneration and heredity, have emerged in the mapping of the city this new arrest institution of social danger. Through a return to legal past / medical status, we sought to demarcate the separation between madness and crime, and with the help of the History of Science, to denature the Judicial Asylum and their fields of knowledge, in addition to the named subject madmen and criminals who integrated their spaces and made possible the realization of their practices.